Cătălin Zamfir, Iancu Filipescu (coord.), Sociologia românească: 1900-2010. O istorie socială, Cluj-Napoca, Editura Eikon, 2015 - Buceanu, Mariana; Simu, Mona (Calitatea Vieții, 2015)
Without abstract.